Association of rs662799 polymorphism with the development of acute cerebrovascular accident in patients with cardiovascular pathology - D. A. Nikulin; A. A. Chernova; S. Yu. Nikulina; A. N. Kelemeneva; V. N. Maksimov (Атеросклероз, 2020)
Objective: to study the association of rs662799 with the development of acute cerebrovascular accident in patients with cardiovascular diseases and risk factors for their development.